Applications of augmented reality in cardiology till 2024: a comprehensive review of innovations and clinical impacts - Ismail Sharieff, Ibthisam; Ravikumar, Diviya Bharathi; Joshi, Shashvat; Sivasubramanian, Barath Prashanth; Gupta, Rajat; Garg, Yash; Thirupathy, Umabalan; Saravanabavanandan, Ragavendar; Yarrarapu, Siva Naga; Samala Venkata, Vikramaditya R. (Frontiers in Virtual Reality, 2025)
IntroductionAugmented reality (AugR) is becoming a widely recognized and innovative platform in global healthcare. AugR has revolutionized cardiology by enhancing the understanding of cardiac structure and function. This review highlights its applications in diagnosis, surgical planning, cardiac procedures, training, rehabilitation, and the future impact of AugR-related technology.MethodsThis review compiles original research and review articles on AugR in cardiology from PubMed till 2024.ResultsAdvancements in visualization and image processing techniques facilitate the development of AugR tools using holographic displays, enhancing diagnostic accuracy and pre-surgical planning. Current AugR tools offer 3D heart imaging for diagnostic procedures, such as assessing Left Ventricular Ejection Fraction (LVEF). AugR enables real-time visualization for congenital and structural heart diseases, aiding in catheter navigation, transcatheter valve procedures, and arrhythmia treatments. Its effectiveness extends to cardiac resynchronization therapy, ventricular tachycardia ablation, and ultrasound-guided catheterization. AugR surpasses standard 2D fluoroscopy in surgical interventions by optimizing fluoroscopic angles, improving pacemaker placement, reducing X-ray exposure, and increasing procedural accuracy. It also enhances medical training by providing immersive experiences for residents and fellows, improving emergency response training. User-friendly AugR technologies effectively engage patients, promote physical activity, and enhance outcomes in cardiac rehabilitation. Further testing of AugR could serve as a pivotal surgical navigation tool in cardiac transplantology. Mixed reality enhances procedural planning and intraoperative navigation in cardiac electrophysiology by providing real-time 3D visualization and spatial orientation. Holographic visualization techniques combined with 3D and 4D printing hold future potential in cardiac care, particularly for designing patient-specific prosthetics. However, widespread clinical adoption of AugR in many healthcare institutions is limited by technical challenges and high costs related to specialized hardware, software, and maintenance.ConclusionAugR holds great promise in transforming cardiac care, but its clinical integration depends on rigorous trials to validate its effectiveness. While much research remains theoretical, increased human testing is essential for real-world applications. Advancing AugR, alongside technologies like 3D/4D printing and holography, could pave the way for a safer and more precise future in cardiology.